Efficacy of Chlorine, Chlorine Dioxide, and Peroxyacetic Acid in Reducing Salmonella Contamination in Wash Water and on Mangoes Under Simulated Mango Packinghouse Washing Operations - Mathew, Elza N.; Muyyarikkandy, Muhammed S.; Bedell, Carley; Amalaradjou, Mary Anne (Frontiers in Sustainable Food Systems, 2018)
Salmonellosis associated with consumption of mangoes have been traced back to the use of contaminated wash water. This highlights the critical role of wash water disinfection in mango processing, affecting its quality, and safety. Moreover, steps unique to the post-harvest handling of mangoes also create a conducive environment for internalization of pathogens into the fruit pulp. Currently, no effective treatment exists to eliminate internalized pathogens from mangoes. Therefore, it is critical to prevent contamination on the fruit to avert pathogen internalization. So the present study evaluated the efficacy of chlorine (200 ppm), peroxyacetic acid (80 ppm) and chlorine dioxide (5 ppm) for reducing Salmonella populations on mangoes and in wash water under simulated mango packing house conditions. Nalidixic-acid resistant isolates of Salmonella Montevideo, S. Newport, S. Baildon, S. Braenderup and S. Poona were used in this study. Disinfectants were added to inoculated wash water (ca.7 log CFU/ml) and mangoes (var. Atualfo and Tommy Atkins) were washed under simulated dump tank wash (24°C for 2 min), hot water treatment (46°C for 75 and 110 min) and hydrocooling conditions (21°C for 30 min). Wash water and mangoes were collected at different times for microbiological analysis. Additionally, residual disinfectant concentration was monitored throughout the study. All the three disinfectant tested were effective in significantly reducing Salmonella populations in wash water and on mangoes during dump tank wash, hot water treatment and hydrocooling (p≤0.05). Specifically, no Salmonella was detected from samples treated with 200 ppm chlorine and 80 ppm PAA. On the other hand, Salmonella was consistently recovered from mango and water samples treated with chlorine dioxide (5 ppm). This reduced antimicrobial efficacy can be attributed to the sharp decline in residual chlorine dioxide concentrations in wash water. Further, reductions in residual chlorine and PAA concentrations were also observed over time. Therefore, to ensure the sustained antimicrobial activity of chlorine and PAA, it is critical to regularly monitor and replenish the disinfectant in wash water. However, given the laboratory scale of these experiments, further validation of these results on a commercial scale are warranted.